2018
DOI: 10.1002/advs.201700876
|View full text |Cite
|
Sign up to set email alerts
|

Painful Terminal Neuroma Prevention by Capping PRGD/PDLLA Conduit in Rat Sciatic Nerves

Abstract: Neuroma formation after amputation as a long‐term deficiency leads to spontaneous neuropathic pain that reduces quality of life of patients. To prevent neuroma formation, capping techniques are implemented as effective treatments. However, an ideal, biocompatible material covering the nerves is an unmet clinical need. In this study, biocompatible characteristics presented by the poly(D,L‐lactic acid)/arginylglycylaspartic acid (RGD peptide) modification of poly{(lactic acid)‐co‐ [(glycolic acid)‐alt‐(L‐lysine)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 61 publications
3
32
0
Order By: Relevance
“…As technology improves, our understanding of the relationship between nerve regeneration and clinically symptomatic neuromas will guide treatment into the near future. The latest technologies include electrospun aligned nanofiber conduits modified with biocompatible peptides to provide a suitable microenvironment to prevent neuroma formation [15]. Our analysis of a bioresorbable polycaprolactone cap is the first in a human model.…”
Section: Resultsmentioning
confidence: 99%
“…As technology improves, our understanding of the relationship between nerve regeneration and clinically symptomatic neuromas will guide treatment into the near future. The latest technologies include electrospun aligned nanofiber conduits modified with biocompatible peptides to provide a suitable microenvironment to prevent neuroma formation [15]. Our analysis of a bioresorbable polycaprolactone cap is the first in a human model.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that silicone tubes, collagen tubes, microcrystalline chitosan, and PRGD/PDLLA conduits can achieve satisfactory effects in preventing traumatic neuroma formation. [22][23][24][25][26][27][28] Hong et al 29 found that acellular nerve allografts (ANAs) attached to the proximal end of an injured nerve can limit axon growth in a controlled manner, indicating that the use of ANAs as a tool to control neuroma formation may be a viable clinical option. In addition, Zhou et al 11 found that the application of a nanofibrous scaffold consisting of aligned silk fibroin blended with poly(l-lactic acid-co-caprolactone) activated the RhoA/ROCK signaling pathway, which contributed to the prevention of traumatic painful neuroma formation because of its suppressive effect on axon regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Neural tissue damages caused by either neurodegenerative diseases or high-energy trauma greatly affect the patients' quality of life worldwide. The mammalian neuronal cells show the limitation of regrowth performance and functional recovery, presenting a critical clinical challenge for surgeons (Yi et al, 2018;Zhang P.-X. et al, 2019).…”
Section: Applications In Neural Tissue Engineeringmentioning
confidence: 99%